Antioxidant activity of methanolic leaf extract of Moringa peregrina (Forssk.) Fiori. - Dehshahri, S. (Medknow Publications & Media Pvt Ltd, 2012)
Natural antioxidants have an important role in the prevention of many age-related diseases and promotion of health. Among natural antioxidants from plants, flavonoids and other phenolic compounds are potent antioxidants and chelating agents. Moringa peregrina (Forssk.) Fiori (Moringaceae) is a small desert tree distributed from tropical Africa to east India. Moringa tree is also growing in south-east of Iran. The antioxidant activity of M. peregrina methanolic leaf extract on 2,2-diphenyl-1-pycrylhydrazyl and superoxide anion radicals was determined in in vitro experiments. It exhibited the scavenging activity on DPPH and superoxide anion radicals with IC(50) of 8.06 ± 0.29 μg/ml and 47.93 ± 1.33 μg/mL, respectively. Moreover, total phenolic content of the leaf extract was determined and using (1)HNMR, mass and spectroscopic methods, the structure of the isolated flavonoid glycoside, rutin, as one of the compounds responsible for reported antioxidant activities was identified.